Authentic assessment in elementary mathematics: A systematic review of task design, effectiveness, and research gaps - Dameis Surya Anggara; Candra Abdillah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Authentic assessment has emerged as an approach that bridges assessment practices with meaningful learning in elementary mathematics education. However, studies integrating task design, effectiveness, and research gaps remain limited. This study aims to systematically synthesize authentic assessment in elementary mathematics, focusing on task design, effectiveness, and future research directions. This research employs a Systematic Literature Review (SLR) guided by PRISMA. Articles were retrieved from Scopus using keywords related to authentic assessment and mathematics education. A total of 48 Scopus-indexed articles were identified, of which 15 were analyzed in depth according to inclusion criteria. Data were analyzed thematically and supported by bibliometric mapping using VOSviewer. The findings indicate that authentic assessment is commonly implemented through performance-based tasks, project-based assessment, portfolios, and rubric-based evaluation. These approaches are effective in enhancing students’ conceptual understanding, critical thinking, problem-solving skills, and engagement in learning. Moreover, authentic assessment provides comprehensive diagnostic information to support differentiated instruction. However, several gaps remain, including limited teacher competence in assessment design, low integration of technology, a lack of culturally responsive assessment, and the scarcity of longitudinal studies. The present study contributes by offering a comprehensive synthesis and proposing directions for developing more adaptive, inclusive, and technology-integrated authentic assessment models in elementary mathematics education.